The Early Results of the Laparoscopic Mini-Gastric Bypass/One Anastomosis Gastric Bypass on Patients with Different Body Mass Index - Mohsen Mahmoudieh; Behrouz Keleidari; Naser Afshin; Masoud Sayadi Shahraki; Shahab Shahabi Shahmiri; Erfan Sheikhbahaei; Hamid Melali (Journal of Obesity)
Introduction. Obesity is among the newest health matters that human beings are struggling with. Length of bypassed intestine is important in achievement of most weight loss and least nutritional and absorptive disorders. This study has aimed to assess short-term metabolic and nutritional effects of laparoscopic mini-gastric bypass/one anastomosis gastric bypass (MGB/OAGB) with a loop bypass length of 180 centimeters (cm) and compare these factors among patients with a body mass index (BMI) of 40–45 and 45–50 kilograms per square meter (kg/m2). Methods. 25 patients were put in group 1 (BMI = 40–45 kg/m2) and 25 patients in group 2 (BMI = 45–50 kg/m2). Patients’ BMI, postoperative weight, excess weight loss, and laboratory tests including fasting blood sugar (FBS), lipid profile, serum iron (Fe), ferritin, total iron-binding capacity (TIBC), 25-OH vitamin D, vitamin B12, liver function tests, and albumin were recorded preoperatively and within 3- and 6-month follow-up. Results. Weight loss and BMI reduction was significantly more in patients with higher BMI level (P=0.007), and excess weight loss was higher in patients with lower preoperative BMI level (P=0.007). Six-month follow-up showed statistically significant reduction in total cholesterol, total triglyceride, Fe, and vitamin B12 among patients with higher BMI level (P value <0.05). Conclusion. Based on this study, 180-cm intestinal bypassed length works for patients with a BMI level of 40–45 and 45–50 kg/m2, according to their significant decrease in weight, BMI, and improving glycolipid profile.